2012
DOI: 10.1186/1471-2407-12-267
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor BLU inhibits proliferation of nasopharyngeal carcinoma cells by regulation of cell cycle, c-Jun N-terminal kinase and the cyclin D1 promoter

Abstract: BackgroundTumor suppressor genes function to regulate and block tumor cell proliferation. To explore the mechanisms underlying the tumor suppression of BLU/ZMYND10 gene on a frequently lost human chromosomal region, an adenoviral vector with BLU cDNA insert was constructed.MethodsBLU was re-expressed in nasopharyngeal carcinoma cells by transfection or viral infection. Clonogenic growth was assayed; cell cycle was analyzed by flow cytometry-based DNA content detection; c-Jun N-terminal kinase (JNK) and cyclin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…The BLU protein is ~50 kDa and contains a MYND zinc finger DNA binding domain at its C-terminus, which was similar to the domains found in transcription repressors such as ETO (MTG8) and BS69 (10)(11)(12). As reported in previous studies, BLU served as a tumor suppressor in human nasopharyngeal carcinoma and ovarian carcinomas via inhibiting proliferation, inducing apoptosis and anti-angiogenic (13)(14)(15)(16). Moreover, BLU was found frequently inactivated by the promoter hypermethylation in various human cancers, which could be restored by demethylating agent 5-Aza treatment (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 56%
“…The BLU protein is ~50 kDa and contains a MYND zinc finger DNA binding domain at its C-terminus, which was similar to the domains found in transcription repressors such as ETO (MTG8) and BS69 (10)(11)(12). As reported in previous studies, BLU served as a tumor suppressor in human nasopharyngeal carcinoma and ovarian carcinomas via inhibiting proliferation, inducing apoptosis and anti-angiogenic (13)(14)(15)(16). Moreover, BLU was found frequently inactivated by the promoter hypermethylation in various human cancers, which could be restored by demethylating agent 5-Aza treatment (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 56%
“…In fact, the function of ZMYND10 protein, its encoded protein, has been reported as inhibitor of colony formation of cancer cells, and found it could be activated by environmental stresses such as heat sock and its regulated by E2F 13 . Moreover, tumor suppressor ZMYND10 inhibits proliferation of NPC cells by regulation of cell cycle, c-Jun N-terminal kinase and the cyclin D1 promoter 19 . Recently, growing evidences proved that the loss of ZMYND10 expression was downregulated correlated with promoter hypermethylation 12,13,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, BLU may suppress the tumor formation and progression via intracellular pathway targeting. Our previous study indicated that BLU downregulated the JNK pathway and inhibited the promoter activity of CCND1 , coding for cyclin D1, hence arresting the cell cycle in G1 phase [ 34 ]. Other studies have shown that BLU also downregulated proangiogenic cytokine to inhibit angiogenesis [ 41 ]; it also inactivated anti-apoptotic members of the Bcl-2 family to promote paclitaxel-induced apoptosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppression of BLU has been indicated by its frequent loss in some human malignancies, but the underlying mechanisms are largely unknown. Previously, we have shown that similar to the tumor suppressors RASSF1A [ 32 ] and NGDR 2 [ 33 ], BLU down-regulates JNK signaling and inhibits the promoter activity of cyclin D1, thereby reducing its expression level to arrest the cell cycle in G1 phase [ 34 ]. The inhibition of cell cycle entry contributes to the proliferation inhibition of BLU .…”
Section: Introductionmentioning
confidence: 99%